A cooperative synchronous observation of winds and tides in the tropical lower stratosphere and mesosphere using VHF radars at Jicamarca and Arecibo - Maekawa, Yasuyuki (1986)
A cooperative synchronous observation of winds in the tropical lower stratosphere and mesosphere was carried out using VHF radars at Jicamarca (11.95°S, 76.87°W) and at Arecibo (18.35°N, 66.75°W) on 19-21 or 23 November 1981. The comparison between observations about symmetrical north and south of the equator is focussed on the mean and tidal wind characteristics. Vertical structures of the mean zonal winds at both observational stations are in fairly good agreement with the CIRA (1972) zonal circulation model at the corresponding latitudes. The nature of lower stratospheric diurnal tides is similar between Jicamarca and Arecibo. Their vertical profiles generally correspond to the theoretical predictions based on the fundamental tidal modes. The vertical scale of the tidal components including higher-order modes is shown to be longer than 10km. In the mesosphere, vertically propagating diurnal tide which is expected to be predominant at lower latitudes is partially detected in daytime at Arecibo, while it is not so well-defined at Jicamarca, suggesting a variable nature of the relevant tidal modes.